KOMUNIKASI GANDA ( DOUBLE CODING) IKLAN SERI REFORMASI : Sebuah Media Promosi sekaligus Propaganda Sosial Politik dari Perusahaan Rokok Sampurna 'A Mild" - Wegig Murwonugroho (Jurnal Dimensi Seni Rupa dan Desain, 2003)
AbstractAdvertisement is considered as a persuasion to consumenr for a product offered. The advertisement is presented in the middle of television programa interuppt public enjoying, especially , the advertisement, which is having a bad impact for helath condition, for intant cigarettte. The negative impression needs to be improved with create a new advertisement model that can give relaxation or as medium of social campaign. This concept provides the basis for A Mild ( cigarette) producer change design perspective of its advertisement as a social campaign medium. The result is manifested ferlection and gives a good impacts to plotical existence in Indonesia , toward politicians, goverment, student, amn also general public